Efeitos de uma intervenção educativa sobre a decisão autônoma e a adoção de comportamento requerido em ensaio clínico: estudo com uma população socioeconomicamente vulnerável - Edna Lucia Campos Wingester (2012)
This research was developed for prepare a vulnerable population to be introduced in a clinical trial. The trial intended to develop a functional food to treat one kind of verminosis.This study aimed to analyze the effect of the educational intervention guided by the social representation of the participants and the Health Action Process Approach (HAPA) model. The following guiding premise here was the intervention by taken-for-granted the socio-cognitive variables of HAPA models - Perception of risk, Expectancy by the results, self-efficacy and Planning made more favorable the autonomous decision by participants and the adoption of behaviors required for the clinical trial. The educational intervention was developed through two educational strategies - a board game and a house constructed by the Lego pieces. The data was collected applying a Socio-cognitive survey (SCS) in two times; the first time the before the education interventions, and the other after interventions. This data was analyzed by Statistical Product and Service Solutions program 14 version (SPSS14). The other test called Mcnemar was used by made a comparison of paired of data. The perception of risk was assessed in terms of the possibility of contracting worms, the possible symptoms and if not treated. The relative susceptibility of the region of residence and habits of life had p 0.05. 81.9% after the intervention began to recognize that they may have worms and no signs and / or symptoms (p 0.05). The expectation of the volunteers with the results was assessed in relation to knowledge about the benefits and risks that would have to join the trial. An understanding of the benefits changes relative to have treatment for other diseases and acquire immunity to participate in the study (p <0.05). Understanding the risks do not change significantly with the intervention. The self-efficacy was assessed as in three distinct stages of adopting a new behavior: compliance, maintenance and recovery. The self-efficacy for volunteers to join and remain in the trial was already high and suffers little variation with emphasis on the readiness to participate in the clinical trial before the intervention. The recovery was altered self-efficacy intervention on educational issues remain in the research even forgetting to perform a task and the need to overcome the difficulties to remain in the study (p <0.05). Ability to plan for participation in the study was assessed in terms of when, how, and what to plan. There was a significant increase in the number of volunteers who recognized the ability to plan the actions of the research thinking how to insert them in your routine (p <0.05). As a result of this research, the data demonstrated that the educational intervention worked in an important way to mediate the adoption of behavior required for the trial research and promoted conditions for exercise of autonomy.